OP45 Continuity of general practitioner care for patients with dementia: impact on prescribing and the health of patients. (26th August 2022) - Delgado, Joao; Evans, Philip; Gray, Denis Pereira; Sidaway-Lee, Kate; Allan, Louise; Clare, Linda; Ballard, Clive; Masoli, Jane; Valderas, Jose; Melzer, David
Abstract : Background: There is no cure for dementia, so finding elements of care that make a difference to patients remains a priority. Treatment of patients with dementia is often complicated by additional medical conditions and they have double the risk of being prescribed inappropriate medication. Higher continuity of general practitioner care (CGPC), that is consulting the same doctor consistently, has shown to improve quality of care received and patients' health outcomes, however, its effects on patients with dementia are mostly unknown. This project estimated associations between CGPC and potentially inappropriate prescribing (PIP) and with the incidence of adverse health outcomes (AHO) in dementia patients. Methods: Retrospective cohort (Clinical Practice Research Datalink) with one year of follow-up anonymised medical records from 9, 324 English patients with dementia, aged 65 years and older in 2016. CGPC measures include Usual Provider of Care (UPC), Bice-Boxerman continuity of care (BB), and sequential continuity (SECON) indices. Regression models estimated associations with PIPs and survival analysis with the incidence of AHOs during follow-up: adjusted for age, sex, deprivation level, 14 comorbidities, and frailty. Results: The highest quartile (HQ) of UPC, those with highest continuity had 34.8% less risk of delirium (OR=0.65, 95%CI=0.51:0.84), 57.9% incontinence (OR=0.42 95%CI=0.31:0.5]), and 9.7% emergency hospitalisations (OR=0.90 95%CI=0.82:0.99) compared with the lowest quartile. Polypharmacy and PIP were identified in 83.1% (N=7612) and 75.1% (N=7027) of patients. The HQ had fewer prescribed medications (HQ: M=8.5, LQ M=9.7;p<0.01) and had fewer PIPs (HQ: M=2.1, LQ: M=2.5:p<0.01) compared to those in the lowest quartiles. Specifically, the HQ was prescribed fewer loop diuretics in patients with incontinence, drugs that can cause constipation, and benzodiazepines with high fall risk. Analyses using BB and SECON produced similar findings. Discussion: Treatment plans are complicated for patients with dementia who often have multiple diseases. Higher continuity of general practitioner care for patients with dementia was associated with safer prescribing and lower rates of major adverse events. Increasing continuity of care for patients with dementia may help improve treatment and outcomes.